Examining financial inclusion success in north India via financial inclusion drivers, financial literacy and financial initiatives: A variance based-SEM approach - Amit Pandey; Ravi Kiran; Rakesh Kumar Sharma (Journal of Open Innovation: Technology, Market and Complexity)
Keeping in view the need to assess the effectiveness of financial inclusion (FI) efforts, this study examines how key drivers of FI—namely usage, digitization, technology, and gender perspective—impact FI success in North India, with financial literacy (FL) as a mediating variable. The study also explores the direct influence of financial initiatives on FI outcomes. Primary data were collected from 1510 customers of public and private sector banks using a standardized questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digitization, technology, and usage are significant FI drivers, and their influence is amplified when mediated through FL. Financial inclusion success is assessed through economic and social empowerment, and results show that financial initiatives positively and significantly contribute to this success. The mediating role of FL further enhances the effect of FI drivers, underscoring the critical importance of financial education in inclusion strategies. These results provide actionable insights for policymakers seeking to expand access to financial services—particularly in underserved rural regions—thereby fostering economic and social empowerment and helping reduce gender and income disparities. Additionally, the findings align with emerging open innovation approaches, advocating for collaborative, technology-enabled, and user-centered financial solutions that can scale inclusivity more effectively.